Misconception about Value-added Tax (VAT) Exemption Policy on Animal Feed in the Flour Industry: An Issue on Self-sufficiency of Meat after Reformation - Raymundus, Torganda; Rosdiana, Haula; Murwendah, Murwendah (Jurnal Politik Indonesia: Indonesian Political Science Review, 2019)
Flour industry and animal feed industry play an important role in supporting government programs to achieve self-sufficiency of meat. The important role of these animal feed producers has triggered the government to stipulate appropriate tax policies to ensure the growth and development of both industries. Through tax policy instruments, the government has provided facilities in the form of Value Added Tax (VAT) exemption for the delivery of animal feed and animal feed ingredients. However, in its implementation, this policy has not been all-inclusive, leading to a cascading effect suffered by the flour industry. It results in an opportunity cost and cost of taxation affecting the productivity of the flour industry as the producer of animal feed. This study applies a qualitative-descriptive method with data collection techniques of in-depth interview and documentation study. This study explains the implications of VAT exemption policy for the flour industry, evaluates VAT exemption policy on animal feed in the perspective of public policy and productivity of animal feed producers, and analyzes political relations and ideas for VAT policy on animal feed in an effort to support national flour industry and animal feed industry